P219 Comparing the sensations and triggers of cough in asthma and idiopathic chronic cough. (12th November 2019) - Saeed, S; Yorke, J; Holt, KJ; Smith, JA; Birchall, DK; Smith, JA
Abstract : Introduction: Cough is a common symptom of many different respiratory diseases. Patients may experience cough as a response to multiple environmental and endogenous triggers, and they often describe associated somatic sensations. Little is known about these sensations and triggers and there are currently no validated questionnaires to assess this. Aims: To explore the differences between the sensations and triggers of cough experienced by groups of patients with asthma or idiopathic chronic cough (iCC). This is in the context of a larger study designed to develop and validate a novel questionnaire that may have diagnostic significance. Methods: Our group are developing the ToPiC (The Sensations Provoking Cough) questionnaire which contains 49 items describing different sensations and triggers of cough. Participants are asked to rate the frequency of each item on a 6 point Likert scale, ranging from 0 (Never) up to 5 (Always). The items are summed to calculate a total TOPIC score with a minimum possible score of 0 and a maximum of 245. In this study all participants were also asked to complete The St George's Respiratory Questionnaire (SGRQ) and a Cough Severity Diary (CSD). All participants were aged over 18 years and had a persistent cough. They were excluded if they had a recent URTI (within 4 weeks) or were taking ACE inhibitors. A Mann Whitney U test was used to compare the ToPiC scores between groups and Spearman's rank correlation was used to investigate relationships with the other questionnaires. Results: Fourty five asthmatics and 49 iCC patients completed the study. The median (IQR) total TOPIC score for iCC patients (101 (77–131)) was significantly higher than for the asthmatics (40(26–49)), p<0.001. There was also a significant positive correlation between TOPIC and SGRQ scores in the asthmatic group (0.319, p=0.033); there was no relationship in the iCC group. ToPiC and CSD scores were unrelated. Conclusion: Differences between TOPIC scores and the lack of correlation with the SGRQ in the iCC group emphasises the need for this questionnaire and its potential value in characterising subjective experiences and cough phenotypes. Further data will be collected in other respiratory disease groups.